Millet: Food of the Himalayas for combating malnutrition in the face of nutritional insecurity - Madhulika Esther Prasad; Sheerat Thapa; Vijay Jagdish Upadhye; Pallavi Singh (Environment Conservation Journal)
Millet is one of the oldest cereal grains, used for several centuries in Asia and Africa. Its ease of growth in adverse environmental conditions and with minimum agricultural inputs made it a popular choice before the advent of the green revolution. However, the green revolution's recent focus on nutritional insecurity has led to a renewed interest in calorie-rich cereal grains like millet. Millet is not only a nutritious grain providing macronutrients and micronutrients, but it also contains health-promoting components such as phenolic compounds, dietary fiber, and resistant starch, benefiting patients with type 2 diabetes, cardiovascular ailments, and celiac disease. In recent years, the approach of biofortification has further guaranteed nutritional enhancement in food crops, including millets, by increasing the concentration of nutrients or reducing the level of anti-nutrients to improve bioavailability. Added to its short life cycle are other advantages, such as drought resistance, durability, insect resistance, and pest resistance. The cultivation of millet offers several environmental benefits, including efficient utilization of water reserves, reduced emission of greenhouse gases (GHGs), CO2 reduction from the atmosphere, and maintenance of soil health and fertility. The Himalayan range in northern India, spanning from west to east across the states of Jammu & Kashmir to Arunachal Pradesh, is known for its traditional millet-based foods, utilizing pearl millet, foxtail millet, finger millet, sorghum, etc., for their food and beverage requirements. In fact, the influence of the Green Revolution in these areas has been minimal due to environmental restrictions on large-scale production of wheat and rice. These Himalayan communities continue to widely use the millet crop, well-adapted to these cold, semi-arid regions, as food, fodder, and beverage for their domestic, cultural, and religious practices. We present a comprehensive understanding of the effectiveness of millet as a nutritious resource in the rural communities of the Himalayan ranges in this review. This paper details the different types of millet-based foods and beverages and the traditional practices used for their production in these rural areas. Promotion of the cultivation and consumption of millet grains can help achieve sustainable development of these rural areas, eliminating hidden hunger, malnutrition, and poverty, and thus attaining Sustainable Development Goals (SDGs) as established by the United Nations (UN). These high-altitude millet populations are part of natural biodiversity which have been subjected to environmental interaction over hundreds of years, and thus, hold potential for revealing new germplasm if explored. Overall, the rural communities of the Himalayan regions hold a traditional treasure in their millet-based foods, which also alleviates the present-day problem of nutritional insecurity.